Life on sticky plants: two new species of Mitrapsylla (Hemiptera: Psylloidea: Psyllidae) on Chamaecrista (Fabaceae) in the Brazilian Highlands - Malenovský, Igor; Serbina, Liliya Š.; Queiroz, Dalva L. (Zootaxa, 2025)
Two new species of the Neotropical jumping plant-louse genus Mitrapsylla Crawford (Hemiptera: Psylloidea: Psyllidae: Ciriacreminae) are described from the highlands of the state of Minas Gerais in the Southeast Region of Brazil. Both species are associated with Chamaecrista (Fabaceae: Caesalpinioideae) and represent the first records of Psylloidea from this plant genus. Chamaecrista, especially its section Absus, has many species endemic to the Cerrado and Caatinga biomes in eastern Brazil. They are characterised by the presence of glandular trichomes that produce sticky secretion that hinders insect mobility and herbivory. Mitrapsylla burckhardtiella sp. nov. is unique within Mitrapsylla because of the long legs and rostrum in the adults and immatures, as well as the details of the tarsus, arolium and claws, the ventral position of the anus, the reduced sectasetae on the caudal plate and the presence of numerous long and thick capitate setae on dorsal sclerites and tubercles in the immatures. These character states are interpreted here as adaptations to living on young leaflets and stems of inflorescences of the densely hairy host plant Chamaecrista ursina, which may help to minimise contact with sticky exudates and camouflage the immatures on the surface of the host plant. In contrast, Mitrapsylla danieli sp. nov. associated with the sparsely haired Chamaecrista hedysaroides lacks these adaptations, and the morphology of adults and immatures is more similar to other Mitrapsylla spp. with non-sticky hosts. The phylogenetic relationships and systematic placement of the two new species within Mitrapsylla and other South American Ciriacreminae are also discussed on the basis of a phylogenetic analysis of the DNA sequences of the mitochondrial COI and cytb gene fragments, which we provide for the first time for four species of Mitrapsylla and two species of Queiroziella Burckhardt. As far as is known, M. burckhardtiella sp. nov. and M. danieli sp. nov. have a limited distribution in the highly diverse but threatened habitats of the Brazilian Cerrado and Campo Rupestre and may be of conservation importance, requiring further study.